Plane Symmetric Inflationary Universe with Hybrid Expansion Law and Time Varying Λ - Wankhade, Rajesh (International Journal of Advanced Astronomy, 2018)
Plane symmetric inflationary cosmological model using Hybrid Expansion Law (HEL) with flat potential and time varying in General Theory of Relativity has been studied. The solution of the Einstein’s field equations is obtained under the assumption of HEL which yields a time-dependent deceleration parameter presenting transition of the universe from the early decelerating phase to the recent accelerating phase. The physical and kinematical parameters of the models have been studied and discussed.